EFEKTIVITAS SOSIALISASI DALAM PELAKSANAAN PEMILU SERENTAK 2024 DI KABUPATEN SIDOARJO - Salsa Nanda Afika; Arini Darajah; Lutfiatul Laili Arrohmati; Julia Putri Anggraini; Syam Rahmanto (Journal Publicuho, 2024)
This study aims to analyze the effectiveness of socialization in the implementation of the 2024 elections in Sidoarjo Regency by using Gibson et al.'s (2003) theory of effectiveness as its analytical tool. This study uses a case study type of research with a qualitative approach. In this study, secondary data sources were used, namely data collected through interviews and observations of the community who participated in socialization activities and primary data obtained from reading materials. The results of the study show that the socialization carried out by the Sidoarjo Regency KPU has succeeded in increasing public participation in the election, as reflected in the increase in the number of permanent voters by 4.58% from 2019. The adaptation of socialization methods through social media and digital content since the COVID-19 pandemic has also proven effective in reaching various levels of society, including remote areas and special communities. Overall, this study confirms that the socialization strategy implemented by the Sidoarjo Regency KPU is effective in supporting the implementation of the 2024 simultaneous elections, and contributes to increasing political participation and public awareness of the importance of elections in Indonesian democracy.